2014
DOI: 10.1159/000364855
|View full text |Cite
|
Sign up to set email alerts
|

No Relative Increase in Intra-Abdominal Adipose Tissue in Healthy Unstressed Preterm Infants at Term

Abstract: Background: Preterm infants may be at risk for altered adiposity, a known risk factor for unfavorable metabolic and cardiovascular outcomes. Objectives: The aim was to compare body composition (total body fat mass (FM), subcutaneous and intra-abdominal adipose tissue (AT)) between infants born preterm and at term. Methods: We conducted an observational, cross-sectional study that involved 50 infants born preterm free from major co-morbidities and 34 term healthy breastfed infants. Anthropometric measurements, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In contrast, a study of 5-7 year preterm-born children reported there was no increase in fat mass or abdominal adiposity compared to term-born children [85]. In another study, preterm-born children had increased total body fat mass at term equivalent age but not increased intra-abdominal adipose tissue when compared to term-born infants [86].…”
Section: Body Composition In Childhood and Adultsmentioning
confidence: 87%
“…In contrast, a study of 5-7 year preterm-born children reported there was no increase in fat mass or abdominal adiposity compared to term-born children [85]. In another study, preterm-born children had increased total body fat mass at term equivalent age but not increased intra-abdominal adipose tissue when compared to term-born infants [86].…”
Section: Body Composition In Childhood and Adultsmentioning
confidence: 87%
“…We also demonstrated that, at birth ( Table 4 ), preterm babies have less BF% and FM and less FFM than their term counterparts. Low FM at birth is clinically important because both very small and late preterm babies accumulate FM by the time they reach “term”-corrected age, and so have higher BF% than term newborns ( 21 , 28 , 29 , 30 , 31 , 32 , 33 ). Preterm babies also have less FFM, which is relevant as reduced FFM levels remain in very preterm boys at least up to 5 years of age ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the main difference between growth-restricted and AGA newborns is in subcutaneous fat; intra-abdominal amounts are similar ( 14 ). Moreover, compared with term infants, the increase in intra-abdominal fat in healthy, preterm infants by the time they reach 40–42 weeks post-conceptual age is small ( 29 ), and preterm infants do not have a higher percentage of intra-abdominal fat by 5–7 years of age ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Modi and colleagues [17] found a positive relationship in preterm infants between the increase in intra-abdominal adipose tissue content at term, which has been associated with cardiometabolic risk factors [18], and illness severity during hospitalization. On the contrary, healthy preterm infants do not show an aberrant intra-abdominal adiposity at term [19]. …”
Section: Discussionmentioning
confidence: 99%